Quantitative Assessment of Calcite Scaling of A Vapour-Dominated Well - Candra, Arya Dwi; Agin, Leonardus Farel Putra; Wicaksono, Wien Pratama Abi (Testing Center for Oil and Gas LEMIGAS, 2025)
Geothermal scaling is a prevalent issue that significantly impacts the efficiency of thermal energy production, drawing considerable attention in the field. Scaling formation is attributed to multiple factors, including variations in pressure and temperature. In this field, scaling deposits have been associated with an observed production decline of approximately 3.2%, posing a substantial challenge to maintaining optimal operational efficiency. This study aims to quantitatively assess the potential for calcite scaling in selected production wells and to estimate scaling growth rates as a basis for determining appropriate well-cleaning intervals. Geochemical data from produced fluids were analyzed to evaluate calcite and silica saturation using saturation indices derived from simplified thermodynamic relationships. Calcite scaling potential was assessed using the Calcite Saturation Index (CSI), while silica scaling was evaluated using the Silica Saturation Index (SSI). The growth rate of calcite deposits was estimated using a kinetic-based Calcite Scaling Thickness (CST) approach. The results indicate that one production well exhibits calcite supersaturation, while silica scaling is not expected under the analyzed conditions. Based on the applied assumptions, the estimated calcite scaling growth rate suggests that periodic well-cleaning interventions are required to maintain production performance. However, the calculations rely on simplified geochemical assumptions, including the use of concentration-based approximations and empirical kinetic parameters. Therefore, the results should be interpreted as an operational estimate rather than a definitive prediction, and further validation using activity-based geochemical modeling and direct scale characterization is recommended. This study provides an operationally oriented framework for linking geochemical indicators to well-maintenance planning in vapour-dominated geothermal fields.